The Gopen–Yang Superior Semicircular Canal Dehiscence Questionnaire: development and validation of a clinical questionnaire to assess subjective symptoms in patients undergoing surgical repair of superior semicircular canal dehiscence. Issue 12 (24th January 2019) - Voth, B L; Sheppard, J P; Barnette, N E; Ong, V; Nguyen, T; Jacky Chen, C H; Duong, C; Arsenault, J J; Lagman, C; Gopen, Q; Yang, I
Abstract: Objective: To characterise subjective symptoms in patients undergoing surgical repair of superior semicircular canal dehiscence. Methods: Questionnaires assessing symptom severity and impact on function and quality of life were administered to patients before superior semicircular canal dehiscence surgery, between June 2011 and March 2016. Questionnaire sections included general quality of life, internal amplified sounds, dizziness and tinnitus, with scores of 0–100 points. Results: Twenty-three patients completed the questionnaire before surgery. Section scores (mean±standard deviation) were: 38.2 ± 25.2 for general quality of life, 52.5 ± 23.9 for internal amplified sounds, 35.1 ± 28.8 for dizziness, 33.3 ± 30.7 for tinnitus, and 39.8 ± 22.2 for the composite score. Cronbach's α statistic averaged 0.93 (range, 0.84–0.97) across section scores, and 0.83 for the composite score. Conclusion: The Gopen–Yang Superior Semicircular Canal Dehiscence Questionnaire provides a holistic, patient-centred characterisation of superior semicircular canal dehiscence symptoms. Internal consistency analysis validated the questionnaire and provided a quantitative framework for further optimisation in the clinical setting.